Changes in Economic Instability in 19th-Century America - James, John A. (American Economic Review, 1993)
In contrast to the 20th century, over the 19th century economic fluctuations became increasingly severe. This paper uses a structural vector autoregression estimated on ante- and postbellum data to distinguish the influences of changes in the nature or magnitude of the disturbances from those of changes in the response of the system to shocks (i.e., changes in structure) in contributing to this increased economic instability. The increased cyclical severity in the postbellum period is found to have been the result of greater sensitivity to monetary disturbances, rather than of larger or more volatile shocks.